Is Universal Grammar Available To L2 Learners? - Boussaid, Youness (International Journal of Language and Literary Studies, 2022)
Nativist argues that Universal Grammar is the genetic component of the language faculty. This theoretical concept is controversial in many aspects. The lack of strong empirical evidence has rendered some language researchers and teachers troubled about what Universal Grammar is and whether L2 learners have access to UG. Understanding the different aspects of UG would assist teachers in approaching teaching L2 learners in the light of UG theory. The present review paper provides a brief account of what UG is and critically investigates the hypotheses and arguments for and against UG to give a comprehensive answer to the question: is universal grammar available to L2 learners? A myriad of hypotheses have been put forward to answer this question. These range from those that suggest that L2 learners have full access to UG in that learners can reset their parameters to conform to L2 parameters to those that suggest that L2 learners only have partial access to UG. Apart from these accounts, others argue that learners acquire L2 using general domain skills rather than direct access to UG. Still, others assert that L2 learners only have access to UG via L1.